Rivaroxaban Versus Warfarin for the Treatment of Cerebral Venous Thrombosis (RWCVT): A Randomized Controlled Trial in Resource-Limited Setting - Ahmad Alkhawam; Lina Okar; Ibrahem Hanafi; Peyton Murin; Ali Ibrahim; Juman Isstaif; Eman Khashaneh; Rami Z. Morsi; Tareq Kass-Hout (Stroke Research and Treatment)
Trial Registration: ClinicalTrials.gov identifier: NCT04569279